2023
DOI: 10.2196/42203
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Mental Health of Chinese Sexual and Gender Minority Women and Cisgender Heterosexual Women: Cross-sectional Survey and Mediation Analysis

Abstract: Background Health-related research on sexual minority populations in China is lacking, and research on sexual and gender minority women (SGMW, including transgender women and persons of other gender identities assigned female at birth of all sexual orientations, and cisgender women with nonheterosexual orientations) is even less. Currently, there are limited surveys related to mental health in Chinese SGMW, but there are no studies on their quality of life (QOL), no studies comparing the QOL of SGM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
1
1
1
Order By: Relevance
“…The results indicated a significant difference in marital status (c 2 = 273.67, p < 0.001) between heterosexual and sexual minority groups. Similar to the previous study, sexual minority participants showed less marriage intention than heterosexual participants in the current study (35). The differences in other demographics were not significant between groups (ps > 0.05).…”
Section: Descriptive and Correlation Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The results indicated a significant difference in marital status (c 2 = 273.67, p < 0.001) between heterosexual and sexual minority groups. Similar to the previous study, sexual minority participants showed less marriage intention than heterosexual participants in the current study (35). The differences in other demographics were not significant between groups (ps > 0.05).…”
Section: Descriptive and Correlation Resultssupporting
confidence: 86%
“…Unlike previous western studies unveiling the mediation effect of the total score of social support or only the score of family support, our results showed that family support and friends' support are prominent protective factors in Chinese sexual minority young men (32,33). Individuals with lower family support and friends' support may face more challenges and become more vulnerable to depressive symptoms and suicidal ideation (35,45,46). An explanation that can account for these results may be that in Asian culture, sexual minority youth were more likely to rely more on family and friends' support rather than support from others.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation